2001
DOI: 10.1038/88236
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Craniometaphyseal dysplasia (CMD) is a bone dysplasia characterized by overgrowth and sclerosis of the craniofacial bones and abnormal modeling of the metaphyses of the tubular bones. Hyperostosis and sclerosis of the skull may lead to cranial nerve compressions resulting in hearing loss and facial palsy. An autosomal dominant form of the disorder (MIM 123000) was linked to chromosome 5p15.2-p14.1 (ref. 3) within a region harboring the human homolog (ANKH) of the mouse progressive ankylosis (ank) gene. The ANK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 0 publications
1
38
0
Order By: Relevance
“…Although the reason for this is not immediately obvious, we hypothesize that elevated P i produced by TNAP hydrolysis of free, unadsorbed (to mineral) PP i could be responsible because P i has been shown to elevate Ank expression in cementoblasts (31). Furthermore, the structure and function of Ank is not entirely clear (20,37), and Wang et al (21) have demonstrated that blocking Ank expression led to increases in both intra-and extracellular PP i levels, whereas Ank overexpression led to decreases in both intra-and extracellular PP i levels, suggesting a level of complexity in PPi handling and homeostasis that needs to be better clarified. Increased Ank expression as a result of increased exogenous PP i could simply be an attempt by the cells to return extracellular PP i levels to normal by as yet an unknown mechanism.…”
Section: Pyrophosphate Inhibits Mineralization Of Mc3t3-e1 Osteoblastmentioning
confidence: 99%
“…Although the reason for this is not immediately obvious, we hypothesize that elevated P i produced by TNAP hydrolysis of free, unadsorbed (to mineral) PP i could be responsible because P i has been shown to elevate Ank expression in cementoblasts (31). Furthermore, the structure and function of Ank is not entirely clear (20,37), and Wang et al (21) have demonstrated that blocking Ank expression led to increases in both intra-and extracellular PP i levels, whereas Ank overexpression led to decreases in both intra-and extracellular PP i levels, suggesting a level of complexity in PPi handling and homeostasis that needs to be better clarified. Increased Ank expression as a result of increased exogenous PP i could simply be an attempt by the cells to return extracellular PP i levels to normal by as yet an unknown mechanism.…”
Section: Pyrophosphate Inhibits Mineralization Of Mc3t3-e1 Osteoblastmentioning
confidence: 99%
“…Third, the antibody used for immunohistochemical staining was generated against the C-terminal 37 amino acid residues of the Ank protein. The topologic organization of Ank in the plasma membrane has not been experimentally determined, but a model proposed by Nurnberg et al (2001) indicates that this C-terminal region is located in the cytoplasm. Therefore, seizure activity could promote an increase in neuronal cell permeability, which would make the antibody epitope more accessible.…”
Section: Seizures Increase Ank Immunoreactivity Throughout the Rat LImentioning
confidence: 99%
“…First, goat anti-Ank polyclonal antiserum was obtained using two synthetic peptides as the antigen. Together these peptides corresponded to the human Ank C-terminal 37 amino acid residues, a region with 100% sequence identity to the murine Ank protein (Ho et al, 2000;Nurnberg et al, 2001). Anti-Ank antibodies were purified and concentrated by passing the serum over an antigen column.…”
Section: Characterization Of Anti-ank Antibodies and Analysis Of Ank mentioning
confidence: 99%
See 2 more Smart Citations